(3eUGHjM GdCfGe aj TQM TQGFY GdESdGes - (3GdHOjQj, GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
... (3bhdg cJGH GdhUGjG hGdfXQ aj Pdc jSJOYj aUhdG GdChd aj GdhUjI hgj Jedjc (B.. (3cd daX Od Ydi Pdc GdbUO cbhdg GYWhG adGfG HeO haGFj Ch dadGf cPG HYO haGFj (B...s
(3BNQgG (B:s
.. (3aZf cGf bdjdG adG jCcd efg TjFG hfMhg Yf JaSjQ GdYjGTj hdcfg eNGda dbGYOI GMJQGe Yed GdeSde hGdefaj GdbGVj(B.. (3hEWdGbG LedI ef GdfUhU hgh Yjf UGdM deYGQVJgG (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\121s
(3eYLe GdeDdajf (B1\486s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis